Quality of Population Document Service in Subang Regency - Komir Bastaman (Universitas Sultan Ageng Tirtayasa, 2021)
The purpose of this study is to provide a description of the service quality of population documents in Subang Regency. The results showed that the Department of Population and Civil Registration of Subang Regency has several tasks related to the quality of population document services in Subang Regency. In this research, the service function is examined from the first point of view, the dimensions of Transparency of Population documents which are currently carried out with Electronic Signatures are conveyed more openly regarding the requirements that must be met and also the completion time set in accordance with the SOP (Standard Operating Procedure). Second, the accountability dimension, the data contained in the Population Administration Information System (SIAK) has not been well integrated with other institutions, so that in terms of responding to public needs and the ability to service Population Documents through Electronic Signatures is not optimal. Third, the conditional dimension, not prioritizing services to people who need Population Documents for the urgent public interest. Fourth, the Participatory dimension, focused on efforts to organize and accelerate programs in each of the Integrated Service Units, this understanding has not been optimal in improving services to the community. Fifth, the dimension of equal rights, in this case the Population and Civil Registration Service, can minimize discrimination in terms of Population Document services. Sixth, the dimension of the balance of rights and obligations is not optimal because service recipients have not met their needs and supervision that should be carried out by direct superiors is often neglected.Keywords: public service; electronic identity card; e-government